A new species of Lysmata (Crustacea, Decapoda, Hippolytidae) from Venezuela, southeastern Caribbean Sea - Baeza, J. Antonio; Bolaños, Juan A.; Hernandez, Jesús E.; López, Régulo (Zootaxa, 2009)
Lysmata udoi n. sp., a new peppermint shrimp, is described from Venezuela, southeastern Caribbean Sea. All individuals were collected from dens of the toadfish Amphichthys criptocentrus (Valenciennes, 1837) in the subtidal zone. This new species can be distinguished from other closely related species of Lysmata by the number of teeth, length and shape of the rostrum, the relative length of the antennular peduncle, and the number of carpal articles of the second pereiopod. The color pattern is distinctive. The fourth abdominal segment almost lacks color, but bears a posterior red thin line with three short forward projections. Morphological and molecular characters demonstrate that L. udoi n. sp. is most closely related to the Gulf of Mexico L. boggessi Rhyne and Lin, 2006 and the Caribbean L. rafa Rhyne and Anker, 2007 and L. ankeri Rhyne and Lin, 2006. Field observations suggest that L. udoi n. sp. is a protandric simultaneous hermaphrodite, with a primary male phase followed by a simultaneous hermaphrodite phase.